Seeing residential (im)mobilities in New York City. - Krase, Jerome (Cultural Studies, 2016)
This chapter discusses and visually demonstrates how ethnicity and class affect residential (im)mobility and how that in turn affects the lives of local residents. It draws on decades long study of New York City's neighbourhoods focused on inter-class and inter-ethnic conflict and competition visible in vernacular landscapes [Krase, J. (2012) Seeing Cities Change: Local Culture and Class, Aldershot, UK, Ashgate; Krase, J. & Shortell, T. (2012) 'On the visual semiotics of collective identity in urban vernacular spaces', in Sociology of the Visual Sphere, ed. D. Zuev & R. Nathansohn, London, Routledge, pp. 108-128]. The mass movement of global capital into New York City has enhanced 'the potential mobility of some, while detracting from the mobility potential of others' [Sheller, M. (2011) 'Mobilities (Review Article)', Sociopedia.isa, [online] Available at: http://mcenterdrexel.wordpress.com/ (accessed 3 August 2013)]. Here, the rich get not only richer, but more mobile as the poor get poorer and less so. Burgess's classic study of the spatial distribution of human activity [1925. 'The growth of the city', in The City, ed. R. E. Park & E. W. Burgess, Chicago, University of Chicago Press, pp. 114-123] has been reinvigorated by the Mobility 'Turn' or 'Paradigm' [Urry, J. (2000) Sociology Beyond Societies: Mobilities for the Twenty-First Century, London, Routledge], which reiterates that spatial and other movements are critical elements of contemporary society.